The Impact of Environmental Performance and Environmental Disclosures on Economic Performance - Fudji Sri Mar'ati; Darsono Darsono (Universitas Negeri Semarang, 2022)
Purpose : This study aims to ascertain how economic performance is impacted by environmental performance and environmental disclosures.Method : The study population consists of LQ45-indexed enterprises registered on the Indonesia Stock Exchange between 2015 and 2019. With a total sample size of 65 financial statement data and annual reports, they were ascertained using the purposive sampling technique. SEM-PLS (Structural Equation Modeling based on Partial Least Squares) data analysis methods with SmartPLS 3.3 were employed for this investigation.Findings : Environmental performance significantly negatively affects economic performance, according to an examination of a study on 13 companies indexed LQ45 in 2015–2019 with 65 financial statement data and annual reports. Ecological transparency, nevertheless, has a very good implication for economic performance. The results of this study have significance for LQ45 firms listed on the Indonesia Stock Exchange, helping them become more environmentally conscious. It can be a strategy for LQ45 companies to get PROPER awards from the government. Additionally, it can serve as a guide when creating environmental rules. Novelty : This study is to measure the economic performance that can be seen from the practice of work on the results of the value of environmental disclosure and environmental performance. This study also explores environmental performance (X1) and environmental disclosure (X2). This study formulates the relationship between environmental performance and the company’s economic performance. And a study of the relationship of environmental disclosure with the company’s economic performance. So that the resulting hypothesis is stronger and more accurate about economic performance resulting from environmental disclosure and environmental performance.Keywords : Economic Performance; Environmental Performance; Environmental Disclosure; LQ45 Companies